Maternal dietary folate, folic acid and vitamin D intakes during pregnancy and lactation and the risk of cows' milk allergy in the offspring. Issue 4 (28th June 2016) - Tuokkola, Jetta; Luukkainen, Päivi; Kaila, Minna; Takkinen, Hanna-Mari; Niinistö, Sari; Veijola, Riitta; Virta, Lauri J.; Knip, Mikael; Simell, Olli; Ilonen, Jorma; Virtanen, Suvi M.
Abstract: Maternal nutrient intake during pregnancy and lactation potentially influences the development of allergic diseases. Cows' milk allergy (CMA) is often the first manifestation of atopic diseases, but the impact of early nutritional influences on CMA has not been explored. The associations between maternal intakes of folate, folic acid and vitamin D during pregnancy and lactation were addressed in a prospective, population-based birth cohort within the Finnish Type 1 Diabetes Prediction and Prevention Study. Mothers of 4921 children during pregnancy and 2940 children during lactation provided information on maternal dietary intake during the 8th month of pregnancy and the 3rd month of lactation using a detailed, validated FFQ. Information on diagnosed CMA in the offspring was obtained from a medical registry as well as queried from the parents. The Finnish food composition database was used to calculate nutrient intake. Logistic regression was applied for statistical analyses. Folate intake and folic acid and vitamin D supplement use were associated with an increased risk of CMA in the offspring, whereas vitamin D intake from foods during pregnancy was associated with a decreased risk of CMA. Thus, maternal nutrient intake during pregnancy and lactation may affect the development of CMA in offspring. Supplementation with folic acid may not be beneficial in terms of CMA development, especially in children of allergic mothers. The association between dietary supplement use and CMA risk can at least partly be explained by increased health-seeking behaviour among more educated mothers who also use more dietary supplements.